Garfield. Bacon me drool - Davis, Jim, 1945 July 28- (Davis, Jim, 1945 July 28- Garfield classics, 2025)
"While Garfield is best known for his insatiable appetite for lasagna, he also believes in making time for bacon, and lots of it. Fans of the fat cat won't want to be disturbed as they happily devour this latest batch of scrumptious comics." --